Long-term outcome of terbinafine and itraconazole in the treatment of onychomycosis [Terbinafin ve i̇trakonazolün onikomikoz tedavisinde uzun süreli i̇zlem sonuçlari] - (:unkn) unknown (My University, 2001)
Background and design: The aim of this study was to compare the efficacy of terbinafine and itraconazole in toenail onychomycosis after a long term follow-up of two years. Materials and methods: A total of 72 patients received either terbinafine 250 mg/day for 12 weeks or itraconazole 200 mg/day for 16 weeks. Clinical symptoms and mycologic outcome were assessed in weeks 4, 8, 12, 16, 24, 36, 48, 96. Forty three patients who completed the study were analysed. Results: At week 48, overall success rates were 95.6% for terbinafine versus 65% for itraconazole (p<0.05). At week 96 overall success rates were 86.9 for terbinafine versus 55% for itraconazole (p<0.05). Conclusion: Terbinafine is still more effective than itraconazole in the treatment of toenail onychomycosis after two years of follow up period.
Keywords: Itraconazole; Onychomycosis; Terbinafine